Determinants of Debt Policy in Indonesia’s Manufacturing Companies - Natasha Claudia Darmawan; Liana Susanto (Graduate Program of Universitas Tarumanagara, 2023)
For manufacturing companies in Indonesia, the goal of this study is to gather empirical evidence to see if institutional ownership has a negative impact on corporate debt policy, if free cash flow has a negative impact on corporate debt policy, if asset structure has a positive impact on corporate debt policy, and if profitability has a negative impact on corporate debt policy. This study collects data using a purposive sample strategy and processes it using EViews 12 SV. Institutional ownership has no impact on corporate debt policy, free cash flow has a negative impact on corporate debt policy, asset structure has a negative impact on corporate debt policy, and profitability has a negative impact on corporate debt policy, according to research conducted on 73 companies between 2017 and 2020.